Efektivitas Transversus Abdominis Plane Block terhadap Skala Nyeri Post Sectio Caesarea di RSUD Raden Mattaher Jambi - Denisa Meiliyanti; Sulistyowati Sulistyowati; Fairuz Fairuz; Ade Susanti; Armaidi Darmawan; Esa Indah Ayudia (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Post-cesarean section (CS) pain is a clinical problem that can hinder early mobilization, breastfeeding, and patient recovery. The Transversus Abdominis Plane (TAP) block is a regional analgesia technique developed as part of multimodal analgesia to reduce postoperative somatic pain following a cesarean section. This study aimed to determine the effectiveness of the Transversus Abdominis Plane (TAP) block on pain scores in patients following a cesarean section at Raden Mattaher General Hospital in Jambi. A prospective cohort study was conducted on 20 patients who had undergone cesarean section (SC), divided into a TAP block group (n=10) and a no-TAP-block group (n=10). Sampling was performed using consecutive sampling. Pain levels were measured using the VAS score at 4, 6, 12, and 24 hours post-surgery. Analysis was performed using the Mann–Whitney test for data that were not normally distributed and the independent t-test for normally distributed data, with a significance level of p<0.05. The TAP block group showed lower pain scores than the group without a TAP block at all observation times. However, there were no statistically significant differences in VAS scores at 4 hours (p=0.178), 6 hours (p=0.054), 12 hours (p=0.230), 24 hours (p=0.298), or in the mean VAS score (p=0.097). A history of cesarean section was significantly associated with pain scores at 24 hours postoperatively. The TAP block has not been statistically proven to effectively reduce the severity of post-cesarean section pain in this study, although it showed a tendency to result in lower pain scores compared to the group without a TAP block